Demographic and economic trends in a rural Europe in transition - Mats Johansson; Pia Nilsson; Hans Weslund (European Regional Science Association (ERSA), 2014)
Rural Europe is in a phase of huge transition both from a demographic and economic-structural point of view. This paper is focused on demographic and economic-structural changes in differing rural areas and the connection between these processes. This does not exclude the relations to urban areas as population changes in rural areas cannot be analyzed without taking the urban population development on board in the analyses. This is of course especially important with regard to the migratory movements where in-migration to urban areas in many cases is dependent of out-migration from rural areas. It has also been shown that rural areas have different migration patterns where many in the surroundings of big cities have experienced a positive population development as an effect of both natural population increase and net in-migration. The contrary is, however, the case in peripheral and remote rural areas where contrary development paths often seem to be the fact. It must here also be highlighted that out-migration also results in eroding reproduction potentials as out-migration of young women accentuate the effects of the drops in fertility. These processes are related to the economic-structural changes both in rural areas and urban ones. Natural population change has, thus, lost its primacy as the dominant factor behind regional population development both in positive and negative ways as the European regions ? urban as well as rural ? have been transformed from high fertility societies to low fertility ones. Instead it is migration that is the prime driver with regard to population development ? both in negative and positive ways in urban as well as rural regions. The 'rural exodus' is in many cases still the rule. In order to analyze and illustrate the differing demographic development paths and the differing preconditions for transformation an economic-structural typology developed within the ESPON/EDORA-project combined with an extended OECD accessibility typology will be used (the Dijkstra-Poelmann typology) by cross-tabulation. This means that distance and accessibility as well as economic and structural traits will be integrated in the analyses of expanding and shrinking regions. The time dimension will be from the beginning of the 1990s up to the latest possible year (2012). The analyses are based on the demographic and economic-structural development at NUTS3-level as this is the lowest level for using quantitative data concerning analyses of demographic and economic-structural changes at a meaningful geographical scale and the connections between these transformation processes in a quantitative way.
Keywords: 330; Shrinking regions; structural transformation; rural areas; migration; reproduction potentials